Transmedia storytelling usage of neural networks from a Universal Design for Learning perspective: A systematic review - Meyerhofer-Parra, Rafel; González-Martínez, Juan (Frontiers in Psychology, 2023)
The use of transmedia storytelling (TST) experiences is increasingly common in today's media ecology. Mediated by participatory culture, the role of the prosumer, and competency processes that connect with the reality of learners, the incorporation of storytelling motivates and deploys diverse didactic strategies. Considering the engagement generated by these strategies, and the need to promote literacies to provide competences to a plural society, a systematic review of the literature on transmedia storytelling experiences from the perspective of universal design for learning (UD-L) using PRISMA is carried out: a priori, we start from the idea that, if UD-L is based on the principles of educational neuroscience and TST, in turn, concretizes some of the guidelines of UD-L, TST can naturally result in a didactic approach that capitalizes on educational neuroscientific knowledge in a harmonious way with the digital context in which we live. The review analyzes a total of 50 articles from four databases: ERIC, Scopus, Web of Science, and Dialnet. The results show a low development of the checkpoints of the UD-L guides, and it is concluded that the most worked checkpoints are those closest to the definition of transmedia storytelling, followed by the foundational aspects of UD-L and, finally, aspects of access. Engagement is reflected in the experiences, but scaffolding is required to consolidate learning. In addition to this is the need to guarantee a true participatory culture, which requires the integration of more elements that incorporate accessibility into didactic strategies, offering learning possibilities for different styles and forms.